Age-related differences in selection by visual saliency - Tsvetanov, Kamen A.; Mevorach, Carmel; Allen, Harriet A.; Humphreys, Glyn W. (Springer, 2013)
We examined the ability of older adults to select local and global stimuli varying in perceptual saliency – a task requiring non-spatial visual selection. Participants were asked to identify in separate blocks a target at either the global or local level of a hierarchical stimulus, while the saliency of each level was varied (across different conditions either the local or the global form was the more salient and relatively easier to identify). Older adults were less efficient than young adults in ignoring distractors that were higher in saliency than targets, and this occurred across both the global and local levels of form. The increased effects of distractor saliency on older adults occurred even when the effects were scaled by overall differences in task performance. The data provide evidence for an age-related decline in non spatial attentional selection of low-salient hierarchical stimuli, not determined by the (global or local) level at which selection was required. We discuss the implications of these results for understanding both the interaction between saliency and hierarchical processing and the effects of aging on non-spatial visual attention.